Exploring Drug Repurposing Through Artificial Intelligence: A Novel Approach to Treating Herpes Zoster Infection - Hinpetch Daungsupawong; Viroj Wiwanitkit (Wolters Kluwer Medknow Publications, 2024)
Background: This study evaluates the potential of ChatGPT, an artificial intelligence (AI) language model, to assist health-care professionals in selecting appropriate medications for the management of herpes zoster. Agroup of experts specializing in dermatology and infectious diseases assess the recommendations provided by ChatGPT for ten hypothetical clinical scenarios involving herpes zoster. Aims and Objectives: The main objective is to determine the extent to which ChatGPT can contribute to informed decision-making when it comes to repurposing drugs for the treatment of this condition. Materials and Methods: The accuracy and relevance of ChatGPT's suggestions are evaluated by comparing them to current medical research and literature. Results: The findings indicate that ChatGPT consistently offers valuable recommendations for potential drug repurposing in the management of herpes zoster, aligning with scientific evidence and published literature. While there may be limitations in terms of therapeutic options and the inability to customize treatment plans, health-care professionals find ChatGPT's guidance beneficial in identifying potential repurposed drugs. However, it is important to address these limitations, such as the need for more clinical data and the ability to customize treatment plans. Further research is necessary to enhance ChatGPT's effectiveness in managing herpes zoster. Conclusion: Future studies should focus on refining the model's capabilities, incorporating comprehensive clinical data, and enabling customization of treatment plans to make ChatGPT a valuable resource for health-care professionals dealing with herpes zoster.